Effect of cooling pad installation on indoor airflow distribution in a tunnel-ventilated laying-hen house - Xue, Hui; Qiang, Zhu; Ni, Ji-Qin; Baoming, Li; Zhengxiang, Shi; Shumei, Zhao; Yu, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Extra cooling pads on the sidewalls are needed for larger poultry houses using tunnel ventilation system. Preliminary study showed that the airflow velocity going through different aisles varies greatly when the extra pads are installed at the end of sidewalls, making a “[”-shape air inlet. Combined with field tests, the CFD (computational fluid dynamics) technology was used to study the uniformity of airflow distribution in a tunnel-ventilated laying-hen house. The air distribution was first monitored in a layer house to find the main reason resulting in the variations of airflows in different aisles. Then CFD simulations were carried out with different distances (D=2 m, 3 m or 4 m) between the pads on end-wall and the extra pads on side walls. The field test showed that airflow streams from the different groups of cooling pads collided vertically at the house corners, mixed with each other, then flew towards the center of the house. This was the main reason that the wind speed in the middle aisle was much higher than in other aisles, leaving large zones of lower ventilation in the aisles adjacent to the sidewalls. The results of CFD simulations indicated that air distributions could be significantly improved when the extra pieces of pads were moved away for an appropriate distance from the end coolingpads. As far as conventional poultry house with a span of 12 m, the air speeds in different aisles were more uniform when this distance was about 3 m.Keywords: Pad cooling system, air distribution, air speed, laying-hen house; CFDDOI: 10.3965/j.ijabe.20160904.2447Citation: Hui X, Zhu Q, Ni J Q, Li B M, Shi Z X, Zhao S M, et al. Effect of cooling pad installation on indoor airflow distribution in a tunnel-ventilated laying-hen house. Int J Agric & Biol Eng, 2016; 9(4): 169－177.